PRODUCTION PERFORMANCE OF PHULE TRIVENI COWS (Indian Journal of Animal Production and Management, 2015)
The data on production performance of 1398 records of Phule Triveni cows maintained at Research Cum Development Project on Cattle, Rahuri were utilized for study. The least squares means of lactation milk yield (LMY), 300 days milk yield (300DMY), lactation length (LL) and dry period (DP) were worked out. The overall mean LMY, 300DMY, LL and DP in Phule Triveni were 3112.15 ± 25.79 kg, 2883.69 ± 20.48 kg, 336.47 ± 1.74 days and 82.34 ± 2.16 days respectively. The period of calving had significant (P
Keywords: Phule Triveni; lactation milk yield; lactation length